Предмет: Алгебра,
автор: Аноним
Упростить:
1)(cos2a+cos(п/2-a)sina)/sin(п/2+a)
2)(1+cos2a+cos^2 a)/sin^2 a
Ответы
Автор ответа:
0
sin^2A+cos^2A=1, cos2a=cos^2A-sin^2A.
sin2a/1+cos2a=(2cosAsinA)/(sin^2A+cos^2A-sin^2A+cos^2A)=2cosAsinA/2cos^2A=
=cosAsinA/cos^2A=sinA/cosA=tgA
Автор ответа:
0
Это второе?
Автор ответа:
0
да
Похожие вопросы
Предмет: Математика,
автор: artyomnikolashyn9
Предмет: Русский язык,
автор: Аноним
Предмет: Биология,
автор: Аноним
Предмет: Обществознание,
автор: uljanatr
Предмет: Информатика,
автор: ErickNight